Randomised trials for the Fitbit generation. Issue 6 (December 2015) - Dempsey, Walter; Liao, Peng; Klasnja, Pedja; Nahum‐Shani, Inbal; Murphy, Susan A.
Abstract : Data from activity trackers and mobile phones can be used to craft personalised health interventions. But measuring the efficacy of these "treatments" requires a rethink of the traditional randomised trial. ByWalter Dempsey, Peng Liao, Pedja Klasnja, Inbal Nahum‐Shani andSusan A. Murphy